2009
DOI: 10.1111/j.1442-200x.2008.02653.x
|View full text |Cite
|
Sign up to set email alerts
|

Head circumference and development in young children after renal transplantation

Abstract: In young children, physical growth, HC growth and DQ scores increased 1 year after transplantation. Dialysis and transplantation program should be planned in young children with end-stage renal failure in anticipation of growth and development of each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…. In another study, an increase of performance IQ within 1 year following KTx was found , and additionally, an increase of head circumference and developmental quotient has been described . These conflicting results might be explained by different ages at time of development of CKD and performance of KTx.…”
Section: Discussionmentioning
confidence: 94%
“…. In another study, an increase of performance IQ within 1 year following KTx was found , and additionally, an increase of head circumference and developmental quotient has been described . These conflicting results might be explained by different ages at time of development of CKD and performance of KTx.…”
Section: Discussionmentioning
confidence: 94%
“…Transplantation has been found to improve deficits present during endstage renal disease, 30,31 particularly physical growth, developmental quotient, and head circumference when measured 1 year after renal transplant. 32 Outcomes in liver transplantation indicate similar developmental delay; children who have had a liver transplant have been shown to have lower intelligence than healthy children, especially when chronic liver disease occurred during infancy. Preliminary data from an ongoing Functional Outcomes Group study using patients in the Studies of Pediatric Liver Transplantation (SPLIT) registry indicate that full-scale IQ in patients who have had a liver transplant are low to normal.…”
Section: Neurocognitive Consequencesmentioning
confidence: 99%
“…One study of pediatric renal transplant recipients reported an FSIQ of 87 (normative mean 100, SD 15) (126). Early renal transplantation has been suggested to improve cognitive function in infants (127). In liver transplantation patients, the FOG/SPLIT group highlighted a high prevalence of cognitive delays and learning problems, with 26% of patients exhibiting ‘mild to moderate' IQ deficits and 4% exhibiting ‘serious delays' (128).…”
Section: Introductionmentioning
confidence: 99%